Design for Disassembly combined with augmented reality for optimization of maintenance processes - Frizziero, Leonardo; Donnici, Giampiero; Freddi, Marco (Frontiers in Sustainability, 2022)
This paper is intended to offer a cue for optimizing a generic disassembly process for maintenance purposes. Through the use of a cutting-edge technology such as augmented reality, a key tool that makes it immediate to tell operators what they need to do, this can be made possible as never before within companies. A first aim of the work is to define the optimal disassembly sequence that can lead to the extraction of a target component of the assembly minimizing the number of parts to be removed, applying two methodologies within the framework of Design for Disassembly. Thus, the most important goal is to show and teach to maintenance technicians which steps they should follow in order to efficiently carry out the repair process built on that sequence so that they can work on a product while learning in parallel what they need to do exactly at the same time. This could be useful in case a component replacement becomes necessary especially because nowadays it is still performed inefficiently and lacks a rigorous logic and methodology aimed at its efficiency in companies.